2014
DOI: 10.1186/1742-4755-11-3
|View full text |Cite
|
Sign up to set email alerts
|

Expanding contraceptive options for PMTCT clients: a mixed methods implementation study in Cape Town, South Africa

Abstract: BackgroundClients of prevention of mother-to-child transmission (PMTCT) services in South Africa who use contraception following childbirth rely primarily on short-acting methods like condoms, pills, and injectables, even when they desire no future pregnancies. Evidence is needed on strategies for expanding contraceptive options for postpartum PMTCT clients to include long-acting and permanent methods.MethodsWe examined the process of expanding contraceptive options in five health centers in Cape Town providin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
42
2

Year Published

2014
2014
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(44 citation statements)
references
References 19 publications
0
42
2
Order By: Relevance
“…All integration models were facility‐based, primarily in HIV care and treatment settings, but also included two clinics for the prevention of perinatal HIV transmission (Hoke et al. ; Sarnquist et al. ).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…All integration models were facility‐based, primarily in HIV care and treatment settings, but also included two clinics for the prevention of perinatal HIV transmission (Hoke et al. ; Sarnquist et al. ).…”
Section: Resultsmentioning
confidence: 99%
“…), the informed and voluntary use of contraception (Hoke et al. ), and the need to support and never dissuade women who want to become pregnant (Phiri et al. ).…”
Section: Resultsmentioning
confidence: 99%
“…98,99 All 12 intervention studies were conducted in sub-Saharan Africa. FP interventions included a facilitated referral model, 61 integration of FP services into HIV clinical care, 62,6468 an education video to promote long-acting methods of contraception, 63,70,71 and group education sessions. 69 …”
Section: Resultsmentioning
confidence: 99%
“…6071 Most of these studies reported significant increases in contraceptive uptake as a result of the intervention, 61,62,6568,70,71 although 2 studies reported null effects. 64,69 Of the 4 studies that included pregnancy incidence as an outcome, 2 found a significant reduction in pregnancy incidence, 68,71 and 2 found no change in pregnancy incidence as a result of the intervention. 62,65 Taken together, these studies provide good evidence that FP interventions can have a high impact on improving contraceptive uptake but the impact on pregnancy incidence remains uncertain.…”
Section: Resultsmentioning
confidence: 99%
“…In the structural domain, healthcare providers often lack clinical guidance, training and support in counselling serodiscordant couples on how to achieve pregnancy safely, or how to integrate training into individualized counselling messages [18,2123]. Additionally, provider training in SRHR service delivery is not always effective due to underlying health system constraints [24]. Lack of knowledge and training among healthcare providers may help to explain reports of stigma and discrimination experienced within the healthcare system by people living with HIV who desire a child, including coercive and forced sterilization [25,26] that are human rights violations [18,27,28].…”
Section: Discussionmentioning
confidence: 99%